DIRECT COSTING–EITHER...OR? - Lentilhon, Robert W. (The Accounting Review, 1964)
The article presents a discussion on the topic related to direct costing, which appeared in the January 1964 issue of the journal The Accounting Review. The paper, like most of its predecessors, had used two opposite poles of inventory and cost measurement, full absorption cost and variable cost. While certainly not the burden of the paper, the impression was left with the reader that these are the two relevant valuation measures to discuss. The author of this article differs with this view. The aim of this paper has been to focus attention on the forgotten third man in the direct versus absorption cost controversy. Standard cost, used with a meaningful fixed overhead application base, can supply useful information, and realistic inventory and income statement values. For many internal management purposes it may also be more useful than the standard cost utilized above. For external reporting, and for other internal management purposes, standard cost, as illustrated in this article, presents possibly more relevant and useful balance sheet inventory value and income statement emphasis.